Employment effects of CAP payments in the UK non-farm economy - Marian Rizov; Sophia Davidova; Alastair Bailey (Rural Policies and Employment: Transatlantic Experiences, 2019)
The effects of the CAP payments on indirectly generated non-farm jobs in small and medium-sized enterprises (SMEs) are central to job creation. This chapter examines whether there are differences in these effects according to business location (rural or urban), the agricultural supply chain, and according to CAP Pillars, using both static and dynamic models of employment. The results suggest positive net spill-overs of CAP payments to non-farm employment. Although their magnitudes are small, they are economically significant. In general, Pillar 1 has a stronger positive employment effect than Pillar 2, but Pillar 2 payments have a stronger positive effect per exteuro spent in rural areas and within the agricultural supply chain.
Keywords: D22; H25; J20; Q18; 330; CAP; non-farm employment; spillovers; SMEs